2011
DOI: 10.1590/s0100-40422011000600028
|View full text |Cite
|
Sign up to set email alerts
|

Polimerização do glicerol: uma reação simples e versátil para produzir diferentes materiais a partir do coproduto do biodiesel

Abstract: INTRODUÇÃOOs polímeros ganharam grande espaço na sociedade no século passado. Nesse período, eles vêm substituindo de maneira crescente diversos materiais tradicionais, como metais, vidro e madeira nos diversos ramos de aplicação, passando pelas indústrias automobilística, eletroeletrônica, têxtil, construção civil, entre outros. 1 Além disso, os polímeros e o seu processo de obtenção apresentam um saudável potencial para aplicação no ensino, especialmente a partir de novas matérias-primas.Os experimentos de l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies have shown that glycerol can be condensed in the presence of acid catalysts to produce ether-type oligomers containing two to five units; [2][3][4][5][6][7][8][9] further reaction leads to the polymerization of glycerol, producing a thermosetting resin. 3,4 Moreover, via glycerol polymerization followed by pyrolysis on the surface of clay vermiculite, a carbon-coated composite with a surface area of 835 m 2 g −1 (essentially microporous, with a significant portion of mesopores) is obtained, and is used for dye adsorption. 10 Polymerization of glycerol produces a thermosetting polymer, which can be pyrolyzed, maintaining its structure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that glycerol can be condensed in the presence of acid catalysts to produce ether-type oligomers containing two to five units; [2][3][4][5][6][7][8][9] further reaction leads to the polymerization of glycerol, producing a thermosetting resin. 3,4 Moreover, via glycerol polymerization followed by pyrolysis on the surface of clay vermiculite, a carbon-coated composite with a surface area of 835 m 2 g −1 (essentially microporous, with a significant portion of mesopores) is obtained, and is used for dye adsorption. 10 Polymerization of glycerol produces a thermosetting polymer, which can be pyrolyzed, maintaining its structure.…”
Section: Introductionmentioning
confidence: 99%